The Cambridge handbook of artificial intelligence - Frankish, Keith; Ramsey, William M., 1960- (Cambridge : Cambridge University Press, 2014)
Artificial intelligence, or AI, is a cross-disciplinary approach to understanding, modeling, and creating intelligence of various forms. It is a critical branch of cognitive science, and its influence is increasingly being felt in other areas, including the humanities. AI applications are transforming the way we interact with each other and with our environment, and work in artificially modeling intelligence is offering new insights into the human mind and revealing new forms mentality can take. This volume of original essays presents the state of the art in AI, surveying the foundations of the discipline, major theories of mental architecture, the principal areas of research, and extensions of AI such as artificial life. With a focus on theory rather than technical and applied issues, the volume will be valuable not only to people working in AI, but also to those in other disciplines wanting an authoritative and up-to-date introduction to the field.
Part I. Foundations : History, motivations, and core themes / Stan Franklin -- Philosophical foundations / Konstantine Arkoudas and Selmer Bringsjord -- Philosophical challenges / William S. Robinson -- Part II. Architectures : GOFAI / Margaret A. Boden -- Connectionism and neural networks / Ron Sun -- Dynamical systems and embedded cognition / Randall D. Beer -- Part III. Dimensions : Learning / David Danks -- Perception and computer vision / Markus Vincze, Sven Wachsmuth and Gerhard Sagerer -- Reasoning and decision making / Eyal Amir -- Language and communication / Yorick Wilks -- Actions and agents / Eduardo Alonso -- Artificial emotions and machine consciousness / Matthias Scheutz -- Part IV. Extensions : Robotics / Phil Husbands -- Artificial life / Mark A. Bedau -- The ethics of artificial intelligence / Nick Bostrom and Eliezer Yudkowsky.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Artificial intelligence -- Philosophy